Bioethanol production using lignocellulose biomass hydrolysate from indigenous fungi fermentation - Farouq, Ahmadu Ali (2012)
The use of fossil fuel for energy purposes is becoming increasingly unreliable,skeptical and environmentally unfriendly while energy generated from foods such as corn and sugarcane is generating crisis of food prices inflation globally. Although,lignocellulose provides a better alternative source for bioethanol, pretreatment of the lignocellulose biomass for efficient enzymatic hydrolysis of the substrates is a major challenge. Pretreatment has been viewed as one of the most expensive processing steps within the conversion of biomass to fermentable sugar. The use of naturally sourced native fungi for the pretreatment of lignocellulose biomass materials is thus a viable alternative devoid of toxic chemicals. In this study, eight native fungi were isolated from Asian elephant (Elephas maximus) dung sourced locally from the natural environment. The isolated fungi were identified morphologically and through the use of molecular assay. All the fungi isolated were further screened for cellulolytic activities and candidate fungi with best cellulolytic activity, namely, T.aureoviride strain UPM 09 and F. equiseti strain UPM 09 were selected and used for pretreatment of lignocellulose biomass materials, namely, rice husk (RH), rubber wood saw dust (RW) and oil palm empty fruit bunch (EFB). Prior to pretreatment,the effect of temperature (30°, 40° and 50°C) on the growth of the fungi was investigated based on optical density (600nm), dry weight and FPase activity. Solid state cultivation (SSC) and submerged cultivation (SMC) methods were used for pretreatment of biomass materials using individual fungi and their consortium.The effect of fungi on pretreatment of biomass materials was analyzed using X-Ray diffraction and scanning electron microscopy. Additionally, cellulase enzymes production was analyzed and the composition of lignocellulose biomass was determined before and after the pretreatment. Following pretreatment, the best pretreated biomass material was selected for bioethanol production using Saccharomyces cerevisiae D5A (ATCC 200062) by Simultaneous Saccharification and Fermentation (SSF). Ethanol production was analyzed using Gas Chromatography. The result of the present study shows that T. aureoviride strain UPM 09 and F. equiseti strain UPM 09 by submerged cultivation (agitated) (SMC) converted about 60-80% of the biomass substrates to glucose thus exhibiting pretreatment and saccharification of the lignocellulose biomaterials simultaneously. GC-MS analysis revealed the presence of volatile hydrocarbons as by-products in the samples of rubber wood saw dust and oil palm empty fruit bunch. F. equiseti strain UPM 09 and T. aureoviride strain UPM 09 produced the highest amount of glucose,reducing sugar with a correspondingly higher amount of enzymes FPase, CMCase, and beta-glucosidase and protein concentration during submerged cultivation (agitated). The results of statistical analysis of the pretreated biomass substrates showed that there was no significant difference (P>0.05) in pretreatment by T. aureovide UPM 09 and Fusarium equiseti strain UPM 09 either individually or in consortium using either SSC or SMC against RH, RW or EFB. The lignin and hemicellulose reduction was 19.9% and 21.17%, 11.17% and 24.97%, and 31.93% and 21.77% for RH, RW and EFB, respectively. Therefore, any of the two fungi can be used for pretreatment purposes either individually or in consortium. Likewise, any of the pretreatment methods can be used. There was also no significant difference (P>0.05) in cellulase production between the two fungi (individually or in consortium) in either SSC or SMC in the three biomass materials used (RH, RW and EFB). In conclusion, the new native fungi can be used in the pretreatment of the lignocellulose biomass materials by submerged cultivation or solid state cultivation using native T. aureoviride strain UPM 09 (JN811061) and F. equiseti strain UPM 09 (JN811063) either individually or in consortium may offer good prospects in the bioethanol production industry by being cost-effective and environmentally friendly. This is because the two fungi each individually and in consortium exhibited a potential for achieving simultaneous pretreatment and hydrolysis of biomass thus shortening the steps in bioethanol production from three to two and at the same time the cost of commercial cellulase enzyme will be reduced. In addition, non-volatile hydrocarbon compounds were produced as by-products by the new native fungi during pretreatment using submerged cultivation. This study provides the first use of native fungi isolates of elephant dung for bioethanol production from lignocellulose biomass in Malaysia.